Professional Development Through Teacher Roles: Conceptions of Professionally Unqualified Teachers in Rural South Africa and Zimbabwe - Tabitha Grace Mukeredzi (Journal of Research in Rural Education, 2013)
Teachers' conceptions of what they learn and how they professionally develop through their teaching roles are key to classroom practice and learner achievement because they influence teachers' pedagogic approaches and choice of materials, content, and learner activities. This article reports on some of the findings from a doctoral research project that explored what 12 professionally unqualified practicing teachers (PUPTs) learned and how they professionally developed through their teaching roles in rural South Africa and Zimbabwe. Drawing on concepts around teacher knowledge and professional development, qualitative data from interviews suggest that these teachers conceived their learning and professional development as revolving around general pedagogic knowledge, pedagogic content knowledge, and knowledge of context emerging out of classroom practice and in-school and out-of-school structures. The article illustrates that policy initiatives to enhance education quality through professional development of PUPTs, particularly in rural schools, may not achieve the intended results if due regard is not given to their conceptions of learning and development through their roles.